Silicon oxycarbide glass-graphene composite paper electrode for long-cycle lithium-ion batteries - David, L.; Bhandavat, R.; Barrera, U.; Singh, Gurpreet (My University, 2016)
Silicon and graphene are promising anode materials for lithium-ion batteries because of their high theoretical capacity; however, low volumetric energy density, poor efficiency and instability in high loading electrodes limit their practical application. Here we report a large area (approximately 15 cm x 2.5 cm) self-standing anode material consisting of molecular precursor-derived silicon oxycarbide glass particles embedded in a chemically-modified reduced graphene oxide matrix. The porous reduced graphene oxide matrix serves as an effective electron conductor and current collector with a stable mechanical structure, and the amorphous silicon oxycarbide particles cycle lithium-ions with high Coulombic efficiency. The paper electrode (mass loading of 2mg cm(-2)) delivers a charge capacity of similar to 588mAhg(-1) (electrode) (similar to 393mAhcm(-3) (electrode)) at 1,020th cycle and shows no evidence of mechanical failure. Elimination of inactive ingredients such as metal current collector and polymeric binder reduces the total electrode weight and may provide the means to produce efficient lightweight batteries.
Citation: David, L., Bhandavat, R., Barrera, U., & Singh, G. (2016). Silicon oxycarbide glass-graphene composite paper electrode for long-cycle lithium-ion batteries. Nature Communications, 7, 10. doi:10.1038/ncomms10998
Keywords: Electrochemical Energy-Storage; Enhanced Rate Capability; Anode; Material; Reversible Capacity; Oxide Paper